Changes in swimming technique during time to exhaustion at freely chosen and controlled stroke rates - Alberty, M.; Potdevin, F.; Dekerle, J.; Pelayo, P.; Gorce, P.; Sidney, M. (Journal of Sports Sciences, 2008)
The aim of this study was to assess technical changes during constrained swimming in time-to-exhaustion tests. Ten swimmers of national standard performed a maximal 400-m front crawl and two sets of exhaustion tests at 95%, 100%, and 110% of mean 400-m speed. In the first set (free), swimmers had to maintain their speeds until exhaustion and mean stroke rate was recorded for each test. In the second set (controlled), the same speed and individual corresponding stroke rate were imposed. The durations of the exhaustion tests, relative durations of the stroke phases, and arm coordination were analysed. For each speed in the "controlled" set, the exhaustion tests were shorter. Moreover, variables were consistent, suggesting a stabilization of stroke technique. Under the free condition, stroke rate increased to compensate for the decrease in stroke length. At the same time, swimmers reduced the relative duration of their non-propulsive phases in favour of the propulsive phases. Thus, swimmers changed their arm coordination, which came close to an opposition mode. These two constraints enable swimmers both to maintain their stroking characteristics and develop compensatory mechanisms to maintain speed. Moreover, stroke rate can be seen as a useful tool for controlling arm technique during paced exercise.